Developing Elementary School Teacher Competence in Making Music Learning Media Using Scratch Application: An Action Research - Julia, J.; Iswara, Prana Dwija; Gunara, Sandie; Agustian, Egi; Yildiz, Yıldız Mutlu (Mimbar Sekolah Dasar, 2020)
The development of technology and information demands elementary school teachers to be able to make and teach technology-based musical instruments so that the development of technology and information can be used in the learning process. Elementary school teachers also have problems teaching musical composition using ensemble musical instruments. Teachers also lack strategies and media to teach musical instruments, so they need to have ideas for developing technology-based musical instruments. This study aims to develop the elementary school teachers’ ability to innovate and make music learning media using a computerized system. The research design used was action research. The participants were 38 teachers from nine regencies and cities in West Java, Indonesia. The results showed that the teachers were able to complete the task of making technology-based learning media which means that they were able to develop their technological abilities to make music learning media. Teachers can easily use and master the Scratch application to make music learning media. It can be concluded that with structured and controlled training, elementary school teachers can develop themselves and innovate well.